Influence of multiple endocrine neoplasia type 1 on gastric endocrine cells in patients with the Zollinger-Ellison syndrome. Issue 9 (September 1992) - Lehy, T; Cadiot, G; Mignon, M; Ruszniewski, P; Bonfils, S
Abstract : The influences of multiple endocrine neoplasia type 1 (MEN 1), hypergastrinaemia, age, and sex on gastric endocrine cell densities were studied in 48 patients with the Zollinger-Ellison syndrome of either the sporadic type (n = 31) or associated with MEN 1 (n = 17). The mean fundic argyrophil cell density was higher in women (p < 0.05). It showed no appreciable difference between young and old women but it declined with age in men. The mean argyrophil cell density, when adjusted for sex, was higher (+48.5%, p = 0.06) in patients with Zollinger-Ellison syndrome associated with MEN 1 than in those with sporadic type disease. This measurement was not significantly different between the two groups of patients when antisecretory treatments were considered. In patients with sporadic type disease, fundic argyrophil cells showed a normal pattern (16%) or diffuse (71%) or linear (13%) hyperplasia. In patients with MEN 1 diffuse and linear hyperplasia were of the same order (53% and 47%). Furthermore, fundic argyrophil endocrine tumours developed in five of 17-that is, 29.5% of patients with associated MEN 1 while none was seen in patients with sporadic type disease. These tumours showed an exclusive or prominent enterochromaffin like cell population. Antral gastrin and somatostatin cell densities and fasting serum gastrin concentrations were similar in the two groups of patients with Zollinger-Ellison syndrome. Whatever the underlying mechanism for carcinoidosis, the risk of developing fundic enterochromaffin like cell tumours in Zollinger-Ellison syndrome patients who present with MEN 1 is probably higher than was initially estimated and suggests that regular follow up of these patients is necessary.